A estação São Francisco nos trilhos do tempo: uma abordagem audiovisual como ferramenta pedagógica para o ensino de História - Rezende, Jeanne do Nascimento (2024)
The present dissertation has as its object of study the São Francisco Station in Alagoinhas (BA), which functioned as a passenger train stop between 1863 and 1989. To this end, in addition to reflecting on the relations between cinema and the teaching of history, an audiovisual product was developed about this historical-cultural monument. The audiovisual product was developed in the format of a short documentary, accessible by QR Code. The general objective of this work is, therefore, to demonstrate to history teachers the potential of audiovisual resources to contextualize local history in the classroom. For this reason, the research used as theoreticalmethodological references, authors such as Jörn Rüsen (2010), Marc Ferro (1992), Jaqueline Zarbato (2018), Marcos Napolitano (2010), among other authors pertinent to the development of our research. The study seeks to contribute to the teaching of history, valuing the local historical source and integrating the regional identity. In addition, it seeks to analyze the use of audiovisual in the contemporary teaching of the discipline, focusing on students of basic education and, for this, using accessible digital media, which can develop significant skills and competencies for teaching-learning.